Oral Anticoagulants in Atrial Fibrillation Patients With Recent Stroke Who Are Dependent on the Daily Help of Others. Issue 11 (27th July 2021) - Meya, Louisa; Polymeris, Alexandros A.; Schaedelin, Sabine; Schaub, Fabian; Altersberger, Valerian L.; Traenka, Christopher; Thilemann, Sebastian; Wagner, Benjamin; Fladt, Joachim; Hert, Lisa; Yoshimura, Sohei; Koga, Masatoshi; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Data on the effectiveness and safety of direct oral anticoagulants (DOACs) versus vitamin K antagonists (VKAs) in patients with stroke attributable to atrial fibrillation (AF) who were dependent on the daily help of others at hospital discharge are scarce. Methods: Based on prospectively obtained data from the observational Novel-Oral-Anticoagulants-in-Ischemic-Stroke-Patients-longterm registry from Basel, Switzerland, we compared the occurrence of the primary outcome—the composite of recurrent ischemic stroke, major bleeding, and all-cause death—among consecutive patients with AF-stroke treated with either VKAs or DOACs between patients dependent (defined as modified Rankin Scale score, 3–5) and patients independent at discharge. We used simple, adjusted, and weighted Cox proportional hazards regression to account for potential confounders. Results: We analyzed 801 patients (median age 80 years, 46% female), of whom 391 (49%) were dependent at discharge and 680 (85%) received DOACs. Over a total follow-up of 1216 patient-years, DOAC- compared to VKA-treated patients had a lower hazard for the composite outcome (hazard ratio [HR], 0.58 [95% CI, 0.42–0.81]), as did independent compared to dependent patients (HR, 0.54 [95% CI, 0.40–0.71]). There was no evidence that the effect of anticoagulant type (DOAC versus VKA) on the hazard for the composite outcome differed between dependent (HRdependent, 0.68 [95% CI, 0.45–1.01]) and independent patients (HRindependent, 0.44 [95% CI, 0.26–0.75]) in the simple model ( P interaction =0.212). Adjusted (HRdependent, 0.74 [95% CI, 0.49–1.11] and HRindependent, 0.51 [95% CI, 0.30–0.87]; P interaction =0.284) and weighted models (HRdependent, 0.79 [95% CI, 0.48–1.31] and HRindependent, 0.46 [95% CI, 0.26–0.81]; P interaction =0.163) yielded concordant results. Secondary analyses focusing on the individual components of the composite outcome were consistent to the primary analyses. Conclusions: The benefits of DOACs in patients with atrial fibrillation with a recent stroke were maintained among patients who were dependent on the help of others at discharge. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03826927.